Kesalahan Terjemahan Konjungtor -te pada Kalimat Majemuk Bahasa Jepang: Kajian Struktur dan Makna - Saidatun Nishfullayli; Wahyu Handayani Setyaningsih (Universitas Gadjah Mada, 2019)
In translating Japanese compound sentences, generally, students still have difficulty in interpreting the meaning of the -te verb which functioned as a conjunction (-te conjunction) in compound sentences. Semantically, the -te verb form has some meanings that can be distinguished based on the context of the sentence. Inaccuracy in determining the meaning of the -te conjunction can affect the results of translating compound sentences. In this research, the forms of -te conjunction translation errors which causes the error in translating compound sentence will be elaborated. Data in this research taken from the translation of 'Haha no Tanjobi', which is one of the subtitles in the Rudolf Beethoven biography book titled Beetoben Kodomo Denki Zenshuu, translated by semester VI students of the Japanese Language Program, Vocational College, UGM. From the analysis, the causes of errors in translating conjunctions can be concluded as follows: learners do not understand the classification of the -te conjunctions’ meaning, lack of mastery of Japanese and Indonesian compound sentence structures, and have not been able to understand the message/ meaning of each clause forming compound sentences in Japanese.